2015
DOI: 10.4238/2015.april.10.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bisphenol A on decreasing the percentage and promoting the growth of stem cell-like cells from SK-N-SH human neuroblastoma cells

Abstract: ABSTRACT. Bisphenol A (BPA) is an industrial contaminant and is reported to be a risk factor associated with the development of tumors. In our previous studies, we have shown that BPA promoted the growth of SK-N-SH human neuroblastoma cells and increased their invasion and metastasis. In this study, we further investigated the effects of BPA and 17b-estradiol (E 2 ) on the stem cell-like cells from SK-N-SH cells. Detection of stem cell markers, proliferation assay, and clonogenic analysis showed that the side-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This statistically significant result concerns all types of tumour combined, which limits the value of these results. However, it is important to highlight that reviewing MACAPEMUR database we found 4 out of the 8 cases observed are neuroectodermal or derived from the neural crest, and there are previous studies that have found associations between SNST and exposures to environmental toxicants such as bisphenol A, polycyclic aromatic hydrocarbons or carbon tetrachloride (Heck et al, 2013; Zheng et al, 2015). Muirhead et al (2015) describe in their study that neuroblastic tumours occur in mini-epidemics where transient environmental exposures, such as infections or air pollution, are involved.…”
Section: Discussionmentioning
confidence: 81%
“…This statistically significant result concerns all types of tumour combined, which limits the value of these results. However, it is important to highlight that reviewing MACAPEMUR database we found 4 out of the 8 cases observed are neuroectodermal or derived from the neural crest, and there are previous studies that have found associations between SNST and exposures to environmental toxicants such as bisphenol A, polycyclic aromatic hydrocarbons or carbon tetrachloride (Heck et al, 2013; Zheng et al, 2015). Muirhead et al (2015) describe in their study that neuroblastic tumours occur in mini-epidemics where transient environmental exposures, such as infections or air pollution, are involved.…”
Section: Discussionmentioning
confidence: 81%
“…In the neuroblastoma cell line SK‐N‐SH, for example, adding 3.75 to 5 µg mL −1 Hoechst significantly induces cell death. [ 20 ] A total of 5 µg mL −1 Hoechst reduces the cell viability of HL‐60 cells to 30% after 24 h. [ 21 ] Erba et al. reported cytotoxic effects of 1.5 µg mL −1 Hoechst on L1210 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐dose BPA exposure results in structural and behavioral changes in the brain, such as decreased dendritic spine density, impaired memory, altered hypothalamic pituitary adrenal (HPA) axis, altered levels of neuronal nitric oxide synthase (nNOS) and steroid receptor, induced aggressiveness, and anxiety . In vivo and in vitro growth‐promoting effects of BPA on SK‐N‐SH cells have also been reported …”
Section: Introductionmentioning
confidence: 99%